SISTEM NILAI DALAM PEMBANGUNAN EKONOMI ADIL DAN BERKELANJUTAN: ANALISIS AKSIOLOGI ISLAM - Husni Shabri; Ivahzada Marella Edgina; Muhammad Said (Tamwil, 2022)
The purpose of this study is to analyze aspects of equitable and sustainable economic development through a system of values with Islamic axiological analysis. The research method uses qualitative methods with data collection techniques using literature studies from various sources in the form of books, journal articles and other documents. The results show that fair, equitable and sustainable economic development has not been able to be realized optimally by the government, development is only concentrated in the city center so that there are still many areas that are categorized as underdeveloped villages, limited facilities and infrastructure in economic activity, educational institutions that do not adequate and the communication network is still difficult. The economic development that has been carried out at this time has not been able to be felt and enjoyed by the entire Indonesian people, only a small number of people enjoy it, so that welfare and justice for all Indonesian people cannot be realized. Zakat and Waqf are financial instruments which are social funds in the Islamic economic system that can be used in alleviating poverty and distributing wealth in realizing equity and justice..